Proposed Marketing Communication Strategy for Fashion Start Up Company (Case Study: LEAMA) - Rifan Maulana, Zulfikar; Rustiadi, Sonny (The Indonesian Journal of Business Administration, 2016)
Abstract . Leama (stylized as LÃ‰AMA) is a start-up fashion company based in Bandung. As a new company, Leama still face several problems in all divisions of the company. In marketing area, brand awareness of Leama is still considered low. This research is aiming to propose marketing communication strategy for Leama in order to increase their brand awareness. First thing to do to address the problem is doing an internal analysis. Research use STP (segmenting, targeting, positioning) and marketing mix (product, price, promotion, place) as tools in internal analysis. In general, Leama segmenting and targeting their market as people who lives in big cities and love to spend leisure time outside their house with positioning statement â€œLeisure Companionâ€. Leama sells leather slippers as their first article, the prices are from IDR 462.000 â€“ 470.000, spreading press release to two online magazine as promotion activities, and only use Instagram as social media and distribution channel. After doing the internal analysis, Leama need to do an external analysis, which consist of Porter 5 Forces analysis, competitor analysis, and benchmark analysis. Porter 5 Forces found that Leama are in high competitiveness level. Competitor and benchmark analysis found that Leama compete with three local competitor who sells product with same theme with Leama. The last is that Leama need to know root cause of the problem using ishikawa/fishbone diagram, with these tools Leama found that never doing sales promotion program and limited ads activities are two main problems. Â To fix these problems, Leama use marketing communication (MC) tools with IMC (Integrated Marketing Communication) approach. Marketing communication tools proposed to Leama are advertising, personal selling, public relation, sales promotion, sponsorship, and trade show. Â Each of these MC tools cannot be stand alone, they are need to integrate with each other in order to gain maximum impact with minimum cost and to make the messages easier to reach the target. The integration between each of MC tools generates several action program that will be held in 2017 which are new year promo, valentine promo, Leama X Fashion Influencer, Trademark Market Event, new article released, Ramadhan promo, independence day promo, Brightspot Market Event, and Leisure Trip Sponsor. Leama future research should be about vendor selection and distribution channel selection. Â Keywords: Marketing Communication Strategy, Fashion, Brand